2014
DOI: 10.1021/jm401653r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectroscopic, and Photophysical Characterization and Photosensitizing Activity toward Prokaryotic and Eukaryotic Cells of Porphyrin-Magainin and -Buforin Conjugates

Abstract: Cationic antimicrobial peptides (CAMPs) and photodynamic therapy (PDT) are attractive tools to combat infectious diseases and to stem further development of antibiotic resistance. In an attempt to increase the efficiency of bacteria inactivation, we conjugated a PDT photosensitizer, cationic or neutral porphyrin, to a CAMP, buforin or magainin. The neutral and hydrophobic porphyrin, which is not photoactive per se against Gram-negative bacteria, efficiently photoinactivated Escherichia coli after conjugation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 49 publications
5
66
0
Order By: Relevance
“…Recently we have reported that some small cationic peptides that had been previously investigated for their antimicrobial activity can be also used as carriers for enhancing the cellular uptake of tetrapyrrolic PSs [4,86]. We conjugated a hydrophobic meso-tetraphenylporphyrin (cTPP), functionalized with a carboxylic group, to the N-terminus of apidaecin 1b (Api), magainin (Mag) and buforin (Buf).…”
Section: Photosensitizers Conjugated To Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently we have reported that some small cationic peptides that had been previously investigated for their antimicrobial activity can be also used as carriers for enhancing the cellular uptake of tetrapyrrolic PSs [4,86]. We conjugated a hydrophobic meso-tetraphenylporphyrin (cTPP), functionalized with a carboxylic group, to the N-terminus of apidaecin 1b (Api), magainin (Mag) and buforin (Buf).…”
Section: Photosensitizers Conjugated To Peptidesmentioning
confidence: 99%
“…Different types of prokaryotic and eukaryotic cells can be killed with this modality provided that the PS has been taken up by the cell or is located in close proximity for allowing the generated ROS to interact with cellular substrates susceptible of photo-oxidative modifications [3,4]. Because of its general or nonspecific mechanism of action, PDT is often proposed for the treatment of various kind of pathological situations.…”
Section: Introductionmentioning
confidence: 99%
“…27). 101 The porphyrin-magainin conjugate increased the binding of the cationic and hydrophilic porphyrins with bacterial cells as indicated by the high photo-inactivation which was retained after Current developments in using meso-(Tetra)substituted porphyrins for PDT 39 washing the bacterial suspension. Solid-phase synthesis and more complex reaction conditions have also found applications in this field.…”
Section: Porphyrin-peptide Conjugatesmentioning
confidence: 99%
“…Anionic and neutral porphyrins are generally not recommended for targeting Gram-negative bacteria due to their poor binding efficacy. However, the association of anionic and neutral porphyrins with Gram-negative bacteria can be considerably improved by the conjugation of cationic antimicrobial peptides (CAMPs) or cell penetrating peptides (CPPs) such as apidaecin [42,43], Tat [44], buforin, or magainin [45] to the PS. These PS-peptide conjugates effectively photosensitized E. coli and induced considerable cell death following APDT compared to unconjugated PS.…”
Section: Porphyrinsmentioning
confidence: 99%
“…Cationic antimicrobial peptides (CAMPs) such as buforin, magainin, and apidaecin are useful antimicrobial peptides that may be conjugated to PSs to improve PS-cell association or intracellular PS delivery [43,45]. The peptides possess bacterial lytic properties and have particular affinity for Gram-negative bacteria.…”
Section: Conjugation Of Cationic Antimicrobial Peptides To Photosensimentioning
confidence: 99%